Analisis Bibliometrik dan Tinjauan Literatur Sistematis Tren Penelitian Perkembangan Material Komposit dalam Bidang Teknik Mesin Berdasarkan Data Scopus tahun 2022-2026 - Mahathir Mahdivikia; M Fauzan Al Fachrezy; Davin Ramadhan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze research trends in composite materials within the field of mechanical engineering during the 2022–2026 period using a Systematic Literature Review (SLR) and bibliometric approach based on VOSviewer and Bibliometrix. The research data were obtained from the Scopus database using queries related to composite materials and mechanical engineering. The literature selection process employed the PRISMA 2020 method, resulting in 3,053 articles that met the inclusion criteria. The findings indicate a significant increase in publication trends each year, with major research focuses on mechanical properties, polymer composites, nanocomposites, and additive manufacturing. Bibliometric analysis revealed that China, the United States, and India were the leading contributing countries. Furthermore, themes such as artificial intelligence, smart composites, and sustainable composite systems have emerged as future research directions. This study provides a comprehensive overview of research trends, scientific collaboration, and research gaps in composite materials development within mechanical engineering.